Preclinical Solid Tumor Models to Study Novel Therapeutics in Brain Metastases. Issue 11 (11th November 2021) - Singh, Mohini; Dahal, Ashish; Brastianos, Priscilla K.
Abstract: Metastases are the most common malignancy of the adult central nervous system and are becoming an increasingly troubling problem in oncology largely due to the lack of successful therapeutic options. The limited selection of treatments is a result of the currently poor understanding of the biological mechanisms of metastatic development, which in turn is difficult to achieve because of limited preclinical models that can accurately represent the clinical progression of metastasis. Described in this article are in vitro and in vivo model systems that are used to enhance the understanding of metastasis and to identify new therapies for the treatment of brain metastasis. © 2021 Wiley Periodicals LLC.